Solution to the Blagaj Tekke Mystery by Ibrahim Opijač of Mostar - Softić, Mejra (Prilozi za orijentalnu filologiju, 2017)
Ibrahim Opijač of Mostar as a philologist and theologian ranked himself, through his works, amongst the acknowledged Bosniak scholars who wrote in Oriental languages. Bearing in mind the speed of solving the Mystery, perceived on a wall of the Blagaj Tekke and the many solutions it offers, there is a feeling that Opijač used the opportunity with unquenchable curiosity to step out for a moment beyond the discipline of the traditional framework of the various commentaries on the works by some other authors, and to refresh his work with his own ideas and thoughts, which later on resulted in the production of his own grammar book. Although written only on a few sheets of paper and in less than one day, Solution to the Blagaj Tekke Mystery is proof of the author.s competent knowledge of Arabic language grammar that enabled him in a way to play with the possibilities of its solution, which have by no means been exhausted, to announce new possibilities and eventually to set the mystery in a new form. Despite the fact that this short philological treatise cannot be defined as a scientific work, every solution offered by Opijač is interesting and has its justification in the grammatical-syntactic rules of the Arabic language. Formally, the solutions are different, but an attentive reader can notice that the differences between their meanings are only in shades. By its value, Solution to the Blagaj Tekke Mystery may by no means be compared with Opijač.s other two works in the field of Arabic, but it can be rightly claimed that it is the author.s knowledgeably formulated answer to those who wanted, as Opijač said at the beginning of the treatise, ..to tempt the men of science in their knowledge.